2022
DOI: 10.1002/ppp.2167
|View full text |Cite
|
Sign up to set email alerts
|

Analytical model to predict unfrozen water content based on the probability of ice formation in soils

Abstract: The variation in unfrozen water content with temperature substantially affects coupled heat and water transport in frozen soil, causing frost heave and thaw settlement owing to the ice and water phase change and influencing soil stability in cold regions. Thus, analyzing the mechanism of water freezing and building a predictive model for the unfrozen water content of soils is paramount. In this study, an analytical model based on equivalent contact angle was developed to predict the unfrozen water content. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The impact of freezing rate and soil volume on the probability of ice formation is much smaller compared to the contact angle (Z. Sun & Scherer, 2010;Wan et al, 2020Wan et al, , 2022, and thus, ΔT sc is primarily determined by the contact angle (θ). Fletcher (1958) and Mullin (2001) suggested that nucleation becomes considerable when J reaches 1 (1/(cm 3 •s)), corresponding to the case of ΔT = ΔT sc ,…”
Section: Pore Water Supercoolingmentioning
confidence: 99%
See 2 more Smart Citations
“…The impact of freezing rate and soil volume on the probability of ice formation is much smaller compared to the contact angle (Z. Sun & Scherer, 2010;Wan et al, 2020Wan et al, , 2022, and thus, ΔT sc is primarily determined by the contact angle (θ). Fletcher (1958) and Mullin (2001) suggested that nucleation becomes considerable when J reaches 1 (1/(cm 3 •s)), corresponding to the case of ΔT = ΔT sc ,…”
Section: Pore Water Supercoolingmentioning
confidence: 99%
“…Kulkarni et al (2012) indicated that the contact angle of mineral particles generally falls between 18°and 24°. Wan et al (2022) suggested that the contact angle during nucleation is related to pore size, with sand having larger pores exhibiting a smaller contact angle compared to clay, resulting in higher nucleation efficiency. Based on the above studies, it is recommended to consider contact angle ranges for different soil types as follows: 14°-22°f or sand, 18°-26°for silt, and 20°-28°for clay.…”
Section: Pore Water Supercoolingmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the above reasons, the study of the water content and ice-water conversion process of lowtemperature frozen coal pores during the melting process of the coal body is crucial for the development and optimization of low-temperature anhydrous permeability enhancement technology for coal seams. This is of great significance for realizing efficient CBM extraction and safe coal mining [20,21].…”
Section: Introductionmentioning
confidence: 99%